2007
DOI: 10.1002/mana.200410520
|View full text |Cite
|
Sign up to set email alerts
|

Lie triple derivations on nest algebras

Abstract: Let δ be a Lie triple derivation from a nest algebra A into an A-bimodule M. We show that if M is a weak* closed operator algebra containing A then there are an element S ∈ M and a linear functional f on A such that δ(A) = SA − AS + f (A)I for all A ∈ A, and if M is the ideal of all compact operators then there is a compact operator K such that δ(A) = KA − AK for all A ∈ A. As applications, Lie derivations and Jordan derivations on nest algebras are characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Lie triple derivations have received a fair amount of attention in recent years, see for example [7,12,15] and references therein. A central problem is whether a Lie triple derivation can be decomposed into a sum of a derivation and a linear map…”
Section: A M B )mentioning
confidence: 99%
See 1 more Smart Citation
“…Lie triple derivations have received a fair amount of attention in recent years, see for example [7,12,15] and references therein. A central problem is whether a Lie triple derivation can be decomposed into a sum of a derivation and a linear map…”
Section: A M B )mentioning
confidence: 99%
“…Results related to Lie triple derivations on prime algebras were considered in [3]. Lu [7] considered similar questions on nest algebras. In Section 4, we characterize Lie triple derivations on triangular algebras and give necessary and sufficient conditions such that every Lie triple derivation is proper.…”
Section: A M B )mentioning
confidence: 99%
“…For Lie triple derivations, Miers [5] showed that every linear Lie triple derivation on a von Neumann algebra without central summands of type I 1 is of the form τ + h, where τ is a linear derivation and h is a Recently, Wang and Lu [6] described the structure of linear Lie triple derivations on J -subspace lattice algebras. For other results, see [7][8][9][10] and the references therein.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, every Jordan triple derivation is an 3 ]. The Lie triple derivations on triangular algebras were studied in [1,7,8,13,16]. These articles are the main motivation for the study of f -derivations on triangular algebras.…”
Section: Introductionmentioning
confidence: 99%